2016
DOI: 10.1186/s13006-016-0091-8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of exclusive breastfeeding practice to infants aged less than six months in Offa district, Southern Ethiopia: a cross-sectional study

Abstract: BackgroundWorld Health Organization (WHO) recommends timely initiation of breastfeeding after birth and only feeding breast milk to infants during the first 6 months of life. It was estimated that exclusive breastfeeding can reduce infant deaths by 13%. The practice of exclusive breastfeeding is suboptimal in many parts of Ethiopia to a varied extent. Factors associated with exclusive breastfeeding practice and the proportion of its practice was not well documented in Offa district. Therefore, this study was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
75
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 18 publications
18
75
0
3
Order By: Relevance
“…Mothers who had at least one ANC visit had 2.24 times significantly higher chance of exclusively breastfeed compared with mothers who had no ANC visit. Egger's regression test for funnel plot asymmetry was not significant (z = 1.69, p = 0.09) (Supplementary Furthermore, seven studies 40,42,47,50,51,53,57 reported the association between EBF and PNC in 2,995 mothers (Table 2C). The pooled OR of PNC was 1.86 (95% CI 1.41 -2.47, p <0.0001, I 2 = 63.4%) ( figure 6).…”
Section: Ebfmentioning
confidence: 97%
See 1 more Smart Citation
“…Mothers who had at least one ANC visit had 2.24 times significantly higher chance of exclusively breastfeed compared with mothers who had no ANC visit. Egger's regression test for funnel plot asymmetry was not significant (z = 1.69, p = 0.09) (Supplementary Furthermore, seven studies 40,42,47,50,51,53,57 reported the association between EBF and PNC in 2,995 mothers (Table 2C). The pooled OR of PNC was 1.86 (95% CI 1.41 -2.47, p <0.0001, I 2 = 63.4%) ( figure 6).…”
Section: Ebfmentioning
confidence: 97%
“…Out of the 24 studies included, 11 studies 23,24,[40][41][42][43][44][45][46][47][48] reported the association between EBF and gender of new-born in 6,527 mothers (Table 2A) Twenty-one studies [33][34][35]38,[40][41][42][43][44][45][46][47][49][50][51][52][53][54][55][56][57] reported the association between EBF and ANC in 16,052 mothers (Table 2B). The pooled OR of ANC was 2.24 (95% CI 1.65 -3.04, p <0.0001, I 2 = 90.9%) ( figure 5).…”
Section: Ebfmentioning
confidence: 99%
“…Besides the practice of exclusive breastfeeding was 78%; affected by maternal education and awareness on the worth of breast milk for children [8]. As shown timely initiation of complementary feeding was also 34% and still maternal education, paternal education and postnatal care visit had ample effect on timely initiation of complimentary feeding [10].…”
Section: Main Textmentioning
confidence: 99%
“…Ahead of shown subjects; determinants of infant and young child feeding (IYCF) practices, occurrence of SAM in under five children and treatment procedures, treatment outcomes of SAM and its predictors were also areas investigated by the researcher [3–5, 7, 8, 10]. The investigations identified the burden of each problem and its key determinants in the studies setting.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the few interventions in which survival benefits extend throughout childhood [3]. Indeed, breast milk is the safest, fullest and most ideal food a mother can offer to her newborn, given that it contains all the nutrients the baby needs in the first six months of life [4].…”
Section: Introductionmentioning
confidence: 99%